Mini Review of the Use of the Mobile Phone and Its Repercussion in the Deficit of Physical Activity - Zagalaz-Sánchez, María Luisa; Cachón-Zagalaz, Javier; Sánchez-Zafra, María; Lara-Sánchez, Amador (Frontiers in Psychology, 2019)
Background Current technology has the ability to distract and evade its users, this resulting in an addiction or “escape” from the real world. The excessive use of smartphones can cause a decrease in physical activity (PA) for many people prefer to use these devices rather than do the recommended physical exercise. Objective The objective of this paper is to analyze the possible relation between the use of smartphones and the reduction in the practice of PA that is reflected in scientific articles. Methods The PRISMA statement has been followed for systematic reviews and meta-analyses in order to achieve a correct organization and integrity of the work. Our search for bibliography has been carried out in the WOS and Scopus databases, together with the research domains “Social Sciences Other Topics,” “Education Educational Research,” and “Sport Sciences.” After applying the inclusion criteria, a total of 14 articles were obtained, these forming the base body of this research. Results Nine of the fourteen articles show that there is a negative relationship between the smartphone and PA practice. The age groups most studied in relation to this topic range from 13 to 18 and from 19 to 25. Conclusion It is our conclusion that the inappropriate use of these mobile devices is associated with low levels of motivation and practice of PA in their users. Similarly, we have emphasized the lack of scientific work dealing with this issue.